PATRIARCHAL CULTURE AND THE CHALLENGES OF WOMEN’S POLITICAL REPRESENTATION IN BALI: A SOCIAL, ECONOMIC, AND POLITICAL ANALYSIS OF BALI LEGISLATIVE ELECTION - Siti Sadiyatunnimah; Maria Bellen Purba (Journal of Social Political Sciences, 2025)
This study examines the impact of patriarchal culture on the low political representation of women in legislative election in Bali. The deeply rooted patriarchal system in Bali contributes to the structural subordination of women in social, economic, and political spheres. Drawing on patriarchal theory and political capital theory, this study conceptualizes women’s marginal political position as the result of gendered power relations that restrict access to social networks, economic resources, and institutional support necessary for electoral competition. Although Hindu philosophy emphasize balance and gender equality, cultural interpretations and daily social practices often position women in subordinate roles. This research employs a qualitative methodology, including in-depth interviews and literature review, to explore the issue comprehensively. Informants include politicians, academics, religious and traditional leaders, women’s rights activists, and local community members. The findings reveal that patriarchal culture significantly shapes women’s limited access and opportunities. Socially, domestic responsibilities and ritual obligations impose a heavy burden on Balinese women, restricting their ability to participate in public activities and political organizations. Economically, women shoulder multiple responsibilities, reducing their capacity to develop political capital. Politically, gender stereotypes, limited networks, high political costs, and the perception of politics as masculine domain significantly hinder women’s participation. Although the 30 percent quota requirement for female candidacy is formally fulfilled, it does not translate into substantive representation. This study contributes theoretically by identifying context-specific gendered political barriers in Bali and offers practical recommendations to strengthen women’s representation in local politics